Conflit foncier, reconfiguration territoriale et valeurs de la terre dans les montagnes de Cahabón (Guatemala) - Agnès Bergeret (Revue de Géographie Alpine)
In the course of half a century, the tropical mountains of Cahabón (a municipality in north-eastern Guatemala) have undergone a radical transformation of their land and agricultural configuration. Accounts from local actors have led us to examine a conflict that has proved to be very violent for the land and whose origins date back to the “colonato” system established at the end of the 19th century. These accounts provide additional elements that help to understand the Guatemalan Civil War (1960-1996), often interpreted through the prism of the Cold War, i.e. counter-revolutionary strategies led by a military regime against communist guerrillas. This article cross-analyses different observation points on a conflict process that has transformed a territory once dominated by a single large coffee estate into a new, highly fragmented configuration of villages populated by small-scale farmers. At each sequence in this process, social and territorial organisation patterns have been transformed by the confrontation between the region’s two local social groups: the mixed-race Ladinos and the native Mayan-Q’eqchi’. The ways in which the mountains have forged the identities of each group and shaped the frameworks of reference and collective actions are key to understanding the strategies adopted by the players in the conflict.